THE ROLE OF INTERCULTURAL COMMUNICATION AND TRANSLATION ACTIVITY IN THE ERA OF GLOBALIZATION - Labuchidze, Dodo (Darejan) (European Scientific Journal, ESJ, 2014)
This article discusses that mondialisation mostly threats the diversity of cultures and languages in the context of intercultural communication and translation activity. The difference between languages only reveals the richness of the divine word and creates all the conditions for each of them to show their potential. It is noted that between cultures one of the substantial contacts are proved by translated monuments, an evident example of which is Georgia where, even in the Middle Ages, the quality and value of the translation activity was taken to the original literature level. In the era of globalization, communication with â€œdominantâ€ cultures and being â€œopenâ€ for them, is indeed a necessary process not only for enrichment of the Georgian culture, but for the purpose of its survival as well; any culture, like language, once not subjected to a change, will no longer fit the new realities, and, is doomed for stagnancy, and therefore, for perishing. In terms of communication between cultures, this situation makes even more important the translation activity; definition of its role sets a new task in a global context of intercultural communication and linguistic-cultural awareness. Like protection of the dignity and rights of all human beings, the modern democratic governance should be the guarantor of cultural values. Thus, it is essential that in the global civilization everyone had opportunity to acquire and be identified in the modernity